2014
DOI: 10.1055/s-0034-1365642
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendokrine Neoplasien der Lunge

Abstract: The pulmonary neuroendocrine neoplasms originate from the enterochromaffin cells which are diffusely distributed in the body. The incidence of these tumors has increased significantly in recent decades due to the available diagnostics. They make up about 1-2% of all lung tumors and 20-30% of all neuroendocrine neoplasms. The current WHO classification from 2004 divides them into typical carcinoids (TC), atypical carcinoids (AC), large cell neuroendocrine carcinomas (LCNEC) and small cell carcinomas (SCLC). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…There were also high and comparable expansions in the Ki-67 expression rates from AC to SCLC/LCNEC for each of the three methods. In the literature it is often described that Ki-67 mainly helps to distinguish low-grade from high-grade BP-NEN [12, 30], but our results also revealed that there was an increase in AC compared with TC. As expected, compared with the Ki-67-Average evaluation, the Ki-67 levels were higher in the Hotspot evaluation in cases of AC, SCLC, and LCNEC, but not TC.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…There were also high and comparable expansions in the Ki-67 expression rates from AC to SCLC/LCNEC for each of the three methods. In the literature it is often described that Ki-67 mainly helps to distinguish low-grade from high-grade BP-NEN [12, 30], but our results also revealed that there was an increase in AC compared with TC. As expected, compared with the Ki-67-Average evaluation, the Ki-67 levels were higher in the Hotspot evaluation in cases of AC, SCLC, and LCNEC, but not TC.…”
Section: Discussionsupporting
confidence: 66%
“…The distinction between the four BP-NEN entities is clinically very important because the subsequent classification-based diagnostic and therapeutic approaches differ due to their differential aggressiveness [3, 5, 6, 29, 30]. Mitosis counting is part of the classification procedure (based on the WHO and IASLC criteria); it is a very time-consuming process, and has a relatively high inter-observer variability [6, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…e increasing variety of diagnostic and therapeutic approaches for patients with TC and AC [31], along with challenges in achieving accurate diagnosis and long-term follow-up of patients, has led to recommendations for a multidisciplinary approach from the care teams, involving collaboration between medical staff with a set of distinct expertise, to ensure each individual patient receives an International Journal of Endocrinology optimal disease management plan [8]. It has been suggested that multidisciplinary care in specialised centres such as ENETS CoE [23], or the North American equivalent (multidisciplinary reference centres) [32], could improve clinical outcomes for patients with TC/AC.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence of thyroid abscess is related to thyroid gland resistance to infection due to its fibrous capsule, high blood perfusion, high iodine contents, and significant lymphatic drainage, and to anatomical separation of the gland from the airway. 1 AST may arise from hematogenous or lymphatic dissemination, continuity from adjacent organs, or direct inoculation after fine needle aspiration (FNA). 2 The predisposing factors vary depending on age at presentation.…”
Section: Case Reportmentioning
confidence: 99%
“…Their incidence has increased significantly in recent decades due to the available diagnostic resources; they represent about 1---2% of all lung tumors and 20---30% of all NET. 1 6-Fluoro-(18F)-l-3,4-dihydroxyphenylalanine (18F-DOPA) is an aminoacid-analog for positron emission-tomography (PET) imaging which has been registered since 2006 in several European Union countries and by several pharmaceutical firms. NET imaging is part of its registered indications.…”
mentioning
confidence: 99%